Bettering writing-reading attainments as to underlying gaps and bonds in EFL learners - Jonathan Olmos; Andres Garcia (Universitas Muhammadiyah Malang, 2023)
With the emergence of new learning approaches, it has become more troublesome learners can pragmatically learn in the long run, especially when learning a foreign language is involved. Flaws and deficiency in learning arises in most cases of EFL classroom where the development language skills like reading and writing are inconclusive. This study aimed to look into the impact of educational practices on the reading and writing skills of learners, with a specific focus on the gaps and bonds in EFL learning while communication skills carried follow-ups. The study employed a mixed methodology, which embraced communication contexts placed in the teaching process, and self-perceptions of the participants in a multidimensional communication axis to collect data via surveys, observational forms and exploratory statistics. The results indicate that while there is a stable level of variation in terms of reading and writing achievement, there are setbacks in certain areas such as fill-in-the-blank questions in complex activities and sentence rewriting tasks. Additionally, the study found that providing students with picture clues can improve their performance. The study also suggests that blending both reading and writing skills in activities can lead to large linkages and improvements in performance.